2020
DOI: 10.1002/ijc.33272
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in ATM, NBN and BRCA2 predispose to aggressive prostate cancer in Poland

Abstract: In designing national strategies for genetic testing, it is important to define the full spectrum of pathogenic mutations in prostate cancer (PCa) susceptibility genes. To investigate the frequency of mutations in PCa susceptibility genes in Polish familial PCa cases and to estimate gene-related PCa risks and probability of aggressive disease, we analyzed the coding regions of 14 genes by exome sequencing in 390 men with familial prostate cancer and 308 cancer-free controls. We compared the mutation frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 33 publications
1
15
1
1
Order By: Relevance
“…When compared with non-BRCA2 carriers, BRCA2 carriers had a significantly higher PPV of PSA >3.0 ng/mL (31% vs 18%; p=0.025), a higher PC incidence rate per 1000 person years (19.4 vs 12.0; p=0.03), a significantly higher frequency of intermediate-high risk PC (p=0.011) and were significantly younger at the time of PC diagnosis (p=0.044), with the youngest age of onset being recorded in a 41-year-old BRCA2 carrier. Overall, the results so far from the ongoing IMPACT study further substantiate the earlier age of onset and more aggressive PC phenotype seen in BRCA2 carriers which has been widely reported throughout the literature, 11,[31][32][33][34]36,87 and also highlights the efficacy of using PSA testing in this patient subgroup.…”
Section: Prostate Cancer Screening In Unaffected Brca2 Mutation Carrierssupporting
confidence: 74%
See 1 more Smart Citation
“…When compared with non-BRCA2 carriers, BRCA2 carriers had a significantly higher PPV of PSA >3.0 ng/mL (31% vs 18%; p=0.025), a higher PC incidence rate per 1000 person years (19.4 vs 12.0; p=0.03), a significantly higher frequency of intermediate-high risk PC (p=0.011) and were significantly younger at the time of PC diagnosis (p=0.044), with the youngest age of onset being recorded in a 41-year-old BRCA2 carrier. Overall, the results so far from the ongoing IMPACT study further substantiate the earlier age of onset and more aggressive PC phenotype seen in BRCA2 carriers which has been widely reported throughout the literature, 11,[31][32][33][34]36,87 and also highlights the efficacy of using PSA testing in this patient subgroup.…”
Section: Prostate Cancer Screening In Unaffected Brca2 Mutation Carrierssupporting
confidence: 74%
“…In addition, a higher proportion of BRCA2+ve tumours have T3/T4 staging (41% (BRCA2+ve) vs 29% (BRCA2-ve), (p<0.001)) and higher rates of metastatic disease at diagnosis (26% (BRCA2+ve) vs 8% (BRCA2-ve), (p<0.001)). A study by Wokołorczyk et al 32 found that PC with Gleason scores >8 were more likely in men carrying germline BRCA2 variants than in non-carriers (75% (BRCA2+ve) vs 22% (BRCA2-ve), (p<0.05)). This group stipulated that BRCA2 carriers had a lower mean age than non- BRCA2 carriers at the time of their PC diagnosis (57 years (BRCA2+ve) vs 61 years (BRCA2-ve), p=0.3).…”
Section: Identification and Management Of Brca2 Deficient Prostate Cancermentioning
confidence: 98%
“…Controls: patients with non-prostate cancers from the same biobank. Not stated Not stated Covariate adjustment for age and genetic ancestry BRCA1 Any pathogenic variant 3/409 (0.73%) Not stated (total: 7711 non-PCa patients) 2.20 (0.62–7.83) Wokolorczyk [ 25 ] Poland 2000–2017 Cases vs controls from the same population Cases: men with PCa who had a family history of PCa in first- or second-degree relatives (three or more relatives with PCa, or two affected relatives of whom at least one was diagnosed before age 60). Controls: participants in an unrelated population-based study.…”
Section: Resultsmentioning
confidence: 99%
“…One case–control study included only cases with a family history of PCa and an unselected control group, and did not adjust for this family history-based ascertainment [ 25 ]. This is likely to lead to higher RR estimates compared to RRs based on case–control studies of unselected cases, because of likely enrichment of PCa PVs in subjects from PCa families.…”
Section: Discussionmentioning
confidence: 99%
“…The ATM-CHEK2-p53 axis acts as a backbone for the DNA damage response (DDR) and is hypothesized to act as a barrier to cancer initiation (Stolarova et al, 2020). Significant associations with familial prostate cancer risk have been reported for both CHEK2 and ATM (Wokolorczyk et al, 2020).…”
Section: Case Studymentioning
confidence: 99%